Analysis Of Factors Related To Response Time Nurses In The Handling Of Emergency Patients In The Emergency Room - Muhammad Ra’uf (Health Media, 2021)
Background : As a nurse that work on emergency department, they are demanded to always do their jobs in any situation and condition that include rescuing patient with professional attitude especially on treating emergency patients. Emergency department as the first gateway to handling emergency case in hospital hold important role on attempt to save patients life. Those respond time have to be taken advantage of to fulfill prime procedure within handling emergency cases or ABCD procedure (Airway, Breathing, Circulation, and Disability). It will able to lessen the spread of internal organ damage and also lessen the cost. Goal : To realize factor that is related to Respond Time on treating emergency patients in Ulin Regional Public Hospital and Dr. Moch. Ansari Saleh Banjarmasin Regional Public Hospital. Meanwhile, independent variables in this research are : age, sex, education, years of service, training, motivation, and job design. Method : Research will use correlation analytic with cross sectional design. The total sampling in this research are 77 responden. Tools that will be used are respond time observation sheet, stopwatch/wristwatch to count responden's respond time, and questionnaire about characteristic, motivation, and nurse's working design in Ulin Regional Public Hospital and Dr. Moch. Ansari Saleh Banjarmasin Regional Public Hospital. Result : Nurses that are inside emergency department which is less than 30 years old are mostly woman, They are mostly have D3 (Diploma 3) education, most nurses also have 5 years of service, and lastly most nurses have BTCLS training. Based on logistic regression analysis, it can be gathered that 1 variable whose have the most common response time are based on age. Implication to nurses : In order to improve nurse's human resourcefulness on subject of emergency, it is hoped that the regarded installation hold training about emergency handling for nurses so that competency, skill, and continually increase nurse's experience and their up-to-date, and also provide facilities and infrastructure that are required within emergency patient needs.